Structural density of the leopard tortoise (Stigmochelys pardalis) shell and its implications for taphonomic research. (August 2019) - Holt, Sharon; Horwitz, Liora Kolska; Hoffman, Jakobus; Codron, Daryl
Abstract: We investigated bone mineral density values of the shell (carapace and plastron) of a modern leopard tortoise ( Stigmochelys pardalis Bell, 1828) to assess its impact on survivorship of the different skeletal elements. We found significant differences among elements for bone mineral density and density volume, but not for bone mineral content. We then compared these findings with those obtained using computed tomography (CT) scans of shells of three modern tortoise species that differ in size and shape; the leopard tortoise, greater padloper ( Homopus femoralis ) and angulate tortoise ( Chersina angulata ). Results indicate that the patterning of bone density is similar across shell elements and scan sites in all species, although all values were lower in the greater padloper, which we attributed to shape differences – a flat rather than domed shell. Finally, we correlated the frequency of shell elements from the Holocene leopard tortoises recovered at the site of Wonderwerk Cave (South Africa) using, as a proxy, the densitometry values obtained from the modern leopard tortoise. For most strata there was a significant association with skeletal element survivorship demonstrating the role played by bone mineral density in determining the skeletal composition of this assemblage. Highlights: Study provides the first bone density values for terrestrial tortoise shell Calculated density using densitometry and CT scans of modern tortoise species Significant association between bone mineral density and shell element survivorship Densitometry values correlate with survivorship of holocene leopard tortoise Application for extant and extinct tortoise taphonomy, biomechanics and function